Editorial: Campylobacter-associated food safety - Zhang, Jingbin; Konkel, Michael E.; Gölz, Greta; Lu, Xiaonan (Frontiers in Microbiology, 2022)
Campylobacter is one of the leading bacterial causes of gastroenteritis worldwide. As the commensal in the gastrointestinal tract of warm-blooded animals, especially food-producing animals, Campylobacter can be transmitted to humans through the food supply chain and cause human campylobacteriosis. Although Campylobacter typically causes self-limiting gastroenteritis, it can also lead to prolonged postinfectious complications, such as Guillain-Barré syndrome, reactive arthritis, and/or post infectious-irritable bowel syndrome, posing a great threat to public health. To address the potential risks associated with this disease, numerous studies have been conducted to improve our understanding of this microbe and its interaction with the agri-food system. This mini-review acts as the editorial summary of the published articles in this special issue collected in Frontiers in Microbiology and provides a brief overview of 1) improved detection methods; 2) prevalence and characterization; 3) novel intervention strategies of Campylobacter in the agri-food settings. This special issue is timely due to the increased recognition of Campylobacter organisms as a serious health threat by the World Health Organization, Centers for Disease Control and Prevention, Health Canada, and European Union.